Plyometric erxercises for overhead-throwing athletes - Pretz, R. (Strength and Conditioning Journal, 2006)
The physical demands of the overhead throw require an athlete to powerfully contract the muscles of the hip, trunk, and shoulder in a proximal-to-distal sequence. This article provides exercises for overhead-throwing athletes, designed to closely mirror those physical demands.